Light–Material Interactions Using Laser and Flash Sources for Energy Conversion and Storage Applications - Park, Jung Hwan; Pattipaka, Srinivas; Hwang, Geon‑Tae; Park, Minok; Woo, Yu Mi; Kim, Young Bin; Lee, Han Eol; Jeong, Chang Kyu; Zhang, Tiandong; Min, Yuho; Park, Kwi‑Il; Lee, Keon Jae; et al. (Nano-Micro Letters, 2024)
This review provides a comprehensive overview of the progress in light–material interactions (LMIs), focusing on lasers and flash lights for energy conversion and storage applications. We discuss intricate LMI parameters such as light sources, interaction time, and fluence to elucidate their importance in material processing. In addition, this study covers various light-induced photothermal and photochemical processes ranging from melting, crystallization, and ablation to doping and synthesis, which are essential for developing energy materials and devices. Finally, we present extensive energy conversion and storage applications demonstrated by LMI technologies, including energy harvesters, sensors, capacitors, and batteries. Despite the several challenges associated with LMIs, such as complex mechanisms, and high-degrees of freedom, we believe that substantial contributions and potential for the commercialization of future energy systems can be achieved by advancing optical technologies through comprehensive academic research and multidisciplinary collaborations. Highlights: 1 This review paper provides a comprehensive analysis of light–material interaction (LMI) parameters, offering insights into their significance in material processing. 2 It examines a wide array of photothermal and photochemical processes, showcasing their versatility in creating advanced materials for energy conversion and storage applications. 3 The review presents a multidisciplinary approach to advancing LMI technologies and highlights their potential contribution to the commercialization of future energy conversion and storage systems.